EFEKTIVITAS MEDIA PEMBELAJARAN UBUR-UBUR TERHADAP PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI MI NURUL HUDA BANJARSARI - muhammad faruq toriqul baihaqi; Rizqiyah Ratu Balqis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of using the ubur-ubur learning media on improving students’ learning interest in Indonesian language subjects at MI Nurul Huda Banjarsari. The background of this study stems from the fact that many students find it difficult to maintain their interest in learning Indonesian, which is often perceived as monotonous and less engaging. This situation leads to low classroom participation, indicating the need for innovative learning media that can foster a more interactive and stimulating learning environment. The research employed a quantitative method with a pre-experimental design, involving one class with a total of 35 students. Data were collected through observation, questionnaires, interviews, documentation, and relevant literature sources. The findings reveal that the use of the ubur-ubur learning media significantly increased students’ interest in learning. This medium encouraged students to be more focused, active, and enthusiastic during the learning process. Furthermore, it created an enjoyable and meaningful classroom experience that enhanced student motivation. These results imply that teachers should develop and utilize innovative learning media as an effective strategy to improve the quality of education at the Madrasah Ibtidaiyah level.